Awareness about the Importance of Nutrition During Pregnancy Among Women in Child Bearing Age: A Quantitative Study Among Urban Women. - Abedulla Khan, Kayamkani; Salem, Maaly; Mohammed, Rawan; Ahmad, Raghad; Abdulkarim, Ola; Mohammed, Tasneem; M. Shakeel Iqubal, S.; Abdullatif Khan, Aejaz; Dawoud, Areej; Sheriff Maqbul, Muazzam; Khan Mayana, Noorulla; Mubashira Begum, Shaik (Journal of Advanced Pharmaceutical Science And Technology, 2020)
Introduction An adequate nutrition pattern is of major importance for one’s health and well-being, especially during pregnancy when a woman undergoes major biological, physical, psychological and social transformations. Macronutrient and micronutrient deficiencies predispose the fetus to preterm birth, neural tube defects, and low birth weight for gestational age. This study was conducted to determine the nutrition awareness of women in childbearing age in order to provide a greater understanding of the life course perspective (LCP) in relation to nutrition behaviors and pregnancy. Methods A cross-sectional study was conducted on based on our conceptualization of nutrition awareness and questionnaire based studies of a face-to-face interview. The participants were women with age group of 17 years to 45 years participate in studies in Jeddah city. Data collection procedures A Semi-structured questionnaires prepared in English language were translated in to Arabic and then translated back to English to check for consistency. The questionnaires were pretested Human ethical committee; the questions assessed respondents’ nutrition knowledge. Results and Discussion Different questions were asked to 175 selected pregnant women to be included in this study assess knowledge of pregnant mothers on nutrition and determinant factors in the study area. Most of the respondents (34.85.2%) were in 19-25 years of age group.69.1 % (n=121) women says they pay attention to the number of soft drinks they drink each day. There would be fascinating to study awareness of specific nutrients and related issues, like consumption folic acid, non-vegetarian diet, minerals and life style such as mental stress and physical exercise.
Keywords: Nutrition; Pregnancy; Nutrition Awareness; Childbearing Age; Macronutrient